Calculation of magnetic field and eddy current loss in end clamping ring of 300MVA synchronous condenser based on a novel semi‐analytical method. Issue 3 (9th December 2022) - Zhu, Erhang; Liang, Yanping; Han, Xiao; Bian, Xu; Wang, Dongmei
Abstract: It is very important to consider the eddy current reaction of the metal structure in large electric machines, which has a direct impact on the calculation results of induced current and loss. In order to solve the problem that the complex end leakage magnetic field is difficult to calculate directly, a new semi‐analytical method (NSM) considering the eddy current reaction is proposed. Firstly, the corresponding relationship between the external magnetic field and the global magnetic field of the clamping ring in two simple calculation models is obtained by the 3‐D finite element method. Then, the external magnetic field of the clamping ring in a 300MVA synchronous condenser under rated operating conditions is calculated, and the global magnetic field of the clamping ring is determined based on the obtained corresponding relationship. The eddy current density and eddy current loss of the clamping ring are calculated using the external magnetic field and the global magnetic field respectively. Finally, the calculation results were compared with the 3‐D finite element results, which verified the importance of the global magnetic field and the accuracy of the NSM. Abstract : In order to solve the problem that it is difficult to directly calculate the complex end leakage magnetic field considering the eddy current reaction, a semi‐analytical method that can quickly calculate the eddy current losses in end metal structures are proposed. The eddy current density and eddy current loss in the clamping ring of 300MVA synchronous condenser are calculated using the external magnetic field and the global magnetic field respectively. The calculation results were compared with the 3‐D finite element results, which verified the accuracy of the proposed method.